Testing Fmr1KO Phenotypes in Response to GSK3 Inhibitors: SB216763 versus AFC03127 - Westmark, Pamela R.; Garrone, Beatrice; Ombrato, Rosella; Milanese, Claudio; Di Giorgio, Francesco Paolo; Westmark, Cara J. (Frontiers in Molecular Neuroscience, 2021)
Glycogen synthase kinase 3 (GSK3) is a proline-directed serine-threonine kinase that is associated with several neurological disorders, including Alzheimer’s disease and fragile X syndrome (FXS). We tested the efficacy of a novel GSK3 inhibitor AFC03127, which was developed by Angelini Pharma, in comparison to the metabotropic glutamate receptor 5 inhibitor 2-Methyl-6-(phenylethynyl)pyridine hydrochloride (MPEP) and the GSK3 inhibitor SB216763 in in vivo and in vitro assays in Fmr1KO mice, a mouse model useful for the study of FXS. The in vivo assay tested susceptibility to audiogenic-induced seizures (AGS) whereas the in vitro assays assessed biomarker expression and dendritic spine length and density in cultured primary neurons as a function of drug dose. MPEP and SB216763 attenuated AGS in Fmr1KO mice, whereas AFC03127 did not. MPEP and AFC03127 significantly reduced dendritic expression of amyloid-beta protein precursor (APP). All drugs rescued spine length and the ratio of mature dendritic spines. Spine density was not statistically different between vehicle and GSK3 inhibitor-treated cells. The drugs were tested over a wide concentration range in the in vitro assays to determine dose responses. A bell-shaped dose response decrease in APP expression was observed in response to AFC03127, which was more effective than SB216763. These findings confirm previous studies demonstrating differential effects of various GSK3 inhibitors on AGS propensity in Fmr1KO mice and confirm APP as a downstream biomarker that is responsive to GSK3 activity.